Neuro-psychophysiological paramenters on imagery, music and sporting performance - Garry Kuan, Pel Ern (Universiti Sains Malaysia, 2018)
The research had been conducted smoothly as scheduled The study 1 and Study 2 had received ethical clearance from Human Research EthiCs Committee. USM (HAEC) with the JEPeM coda USM/JEPer..-111403120. Study 1's data collected had completed on the 2nd February 2015. The literature review of the study was presented to as Keynote speaker at the 3rd National Conference on Sport Pedagogy. Umversity of Ph•hPPI"*S. Man1la, frorn 7th-9!h November 2014. and 2 "Invited speaf..er· at the International Congmss of Sports Psychology. at Sir Shankar Lal Hall. Umversity of Delh1. lnd1a. from 15th-18th October 2014. the 1~ lmemational Scm•nar 1n Physical and Mental Health. Ramkhamhaeng Umversrty, Thailand on the 16th December 2014 The preliminary results from study 1 was presented at the 7th Asian South Pacific Assoc•atiOn of Sport Psychology lntematlonal Congress. 7th- 10th August, 2014 : Tokvo. Japan, and 1Oth lntemaUonal Sports Science Conferece 25-27th August2014 Kola Bharu. Malaysia Completed Study 3. Two long abstract publiShed at the 4th lntemauonal S€m1nar on Sport and Exet'CISe Psychology. which sludent Luke N1kol won best presenter at the seminar. One JOUrnal paper submitted to coach1ng JOUrnal, and one paper published at Plos OneImpact factor 3.234 (01 ). Allolher Paper entitled: Effects of relaxmg and arousing mustc dun11g 1magery tra:mng on dart-throwing performance phys1ologicat arousal md1ccs. and compclihvc state anK1ety. had published at Fronber of Psyc.hology -lmpau factor 2.321 (01).